Biochemical alterations in Horses Infected with Theileria equi - Vidhyalakshmi, TM; Raval, SK; Parikh, PV; Patel, PV (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Equine theileriosis, an OIE listed disease caused by Theileria equi is an economically important haemoprotozoan disease of horses in tropical and subtropical parts of the world. The aim of the present study was to monitor the biochemical alterations in order to find out the severity of the disease. Standard assay kits were used to study the biochemical parameters of horses positive for theileriosis in comparison with healthy ones. Out of 75 serum samples, 25 samples were collected from horses positive for theileriosis and 50 from healthy horses. The serum levels of GPT (32.00±2.30 U/L), GOT (350.84±27.87 U/L), GGT (20.95±0.92 U/L), LDH (823.74±102.93 U/L), total protein (8.11±0.37 g/dl), globulin (3.84±0.40 g/dl), BUN (46.26±5.27 mg/dl) and creatinine (1.33±0.18 mg/dl) were found to be significantly increased (p0.05) in total bilirubin (1.08±0.14 mg/dl), unconjugated bilirubin (0.57±0.11 mg/dl) and glucose (102.57±30.41 mg/dl) as well as non-significant reduction (p>0.05) in conjugated bilirubin (0.42±0.04 mg/dl), albumin (4.26±0.24 g/ dl) and A/G ratio (1.55±0.30) were also observed in infected group. There was no significant alteration (p>0.05) in the level of serum calcium (12.32±0.36 mg/dl) and phosphorus (4.53±0.33 mg/dl), as compared to the healthy group. Significant elevation of GOT, GPT, GGT, BUN and creatinine revealed the involvement of liver and kidney functions in T. equi infected horses. animals gets lowered and poor farmers suffer Equine piroplasmosis caused by Theileria equi is a tick-transmitted haemoprotozoan disease of equids (horse, pony, donkey, and mule) occurring in most tropical and subtropical regions of the world (Boldbaatar et al., 2005) as well as in temperate zones, and poses a serious threat to equine health. The economic importance of this disease is concerned with weakness and inability of horse to work, cost of treatment and deaths (Salib et al., 2013). Due to the carrier status of infection, the draught ability of these economically (Kumar et al., 2013). The aim of the present study was therefore to explore biochemical alterations indicating extent of involvement of various organs which may contribute to the future diagnostic as well as therapeutic approaches in cases of equine theileriosis.
Keywords: Serum biochemistry; Equine merozoite antigen; PCR; Standard assay kits; Theileria equi.